دراسة تحليلية لاجراءات تحصيل عائدات الجباية المحلية دراسة حالة المديرية الولائية للضرائب بالاغواط - برابح نبيلة; عزوزي لحسن; بساس أحمد (جامعة عمار ثليجي الاغواط, 2022)
This study aimed to provide a theoretical framework for the concepts related to the collection procedures and the components of local collection and everything related to them, targeting through the analytical study of the local collection revenues subject to fiscal collection procedures at the level of the Public Prosecution Office of Collection in Laghouat to know the extent of the application of both voluntary and compulsory collection procedures, to conclude However, the collections of taxes and fees belonging to local communities are characterized by their abundance and low yield during the study period because the tax collection interests depend on voluntary collection procedures without completing the compulsory procedures legally authorized for tax collectors. Which compels many taxpayers to seek payment of the amounts they owe by subscribing to installment schedules after understanding with tax collectors, but many subscribers do not abide by what they pledged to stop the follow-up procedures at this level.